Yeast community composition impacts on tequila industry waste treatment for pollution control and waste-to-product synthesis - Díaz-Vázquez, Diego; Garibay, Marycarmen Verduzco; Fernández del Castillo, Alberto; Orozco-Nunnelly, Danielle A.; Senés-Guerrero, Carolina; Gradilla-Hernández, Misael Sebastián (Frontiers in Chemical Engineering, 2022)
The Tequila industry is a major producer of wastewater in the state of Jalisco, Mexico. Tequila vinasses (TV) are a residue from the distillation of fermented agave wort during tequila production. TV are difficult to treat due their high organic content, high nutrient loads, acidic pH and high discharge temperature. TV are frequently released into waterbodies or soil without any treatment, leading to environmental degradation of soil and water sources. To reduce the environmental impact of the tequila industry, cost-effective TV revalorization approaches must be developed. The goals of the present study were to assess the treatment and revalorization potential of TV using mono and mixed yeast cultures to produce single-cell protein (SCP) and to analyze yeast community composition using high-throughput sequencing during the mixed-culture fermentation of TV. The fermentation process was performed using a mixed culture of three fodder yeast species (Candida utilis, Rhodotorula mucilaginosa and Kluyveromyces marxianus) during 48 hrs at benchtop-scale. High-throughput sequencing was performed to assess the relative abundance of the yeast communities. Additionally, a redundancy analysis was performed to analyze the bidirectional influence between yeast communities and pollutant removal (COD, nitrogen, phosphorus, proteins, and sugars). Mixed yeast cultures displayed overall higher pollutant removal rates than monocultures, where C. utilis and K. marxianus contributed the most to pollutant removal and protein accumulation. The R. mucilaginosa population declined rapidly in mixed culture, presumably due to TV acidity and phenolic composition. However, the presence of The R. mucilaginosa in the mixed culture enhanced pollutant removal and amino acid contents. Accordingly, the protein and amino acid content within mixed cultures were significantly higher than those of monocultures, indicating that mixed cultures have a strong potential to produce protein rich biomass from TV, aiding in the transition of both the tequila and the livestock industries to a sustainable circular bioeconomy model by the reintegration of organic material flows into productive processes, reducing raw resource intake and waste generation. The present circular bioeconomy approach could represent a potential to produce 45,664 tons of protein feed yearly, based on the current tequila vinasses generated in the state of Jalisco.